In Vitro Cestocidal Activity of Thymol on Mesocestoides corti Tetrathyridia and Adult Worms - Maggiore, M.; Elissondo, M. C. (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Nothing is known about the possible effect of thymol or other compounds of essential oils against the adult worms of cestodes. The aim of the present work was to determine in vitro cestodicidal activity of thymol against Mesocestoides corti adult worms. Moreover, the in vitro effect on tetrathyridia was also demonstrated. Tetrathyridia exposed to different concentrations of thymol showed a concentration and time-dependent effect. At lower concentrations, the main change observed was mainly in morphology, with larvae exhibiting an elongation of the body. When tetrathyridia were exposed to higher concentrations, increased surface alterations and damage were detected. The body appeared elongated and flattened, and a complete loss of morphology and microtriches was observed. Thymol was able to kill M. corti tetrathyridia, since following inoculation of treated parasites in mice no parasites could be recovered. The effect on M. corti adult worms was dose and time-dependent. Changes in motility coincide with the tissue damage were observed at the structural and ultrastructural level. Thymol caused severe damages to both developmental stages analyzed. Damages were more significant in fully segmented worms. The data reported in this paper demonstrate a clear in vitro effect of thymol against M. corti tetrathyridia and adult worms.